ANALYSIS OF RESPONSIBLE TOURISM MARKETING TOWARD ENTREPRENEUR IN CULINARY SECTOR OF TOURISM - Agustinawati; Halida Bahri; Laila Fajri; Danyatul Hayati; Ghufran Mutahallil (RADJA PUBLIKA, 2022)
The responsible tourism marketing mix strategy must be able to create dimensions of business opportunities (entrepreneurship) for local communities in tourism activities. This study aims to investigate the infleunce of responsible tourism marketing mix on entrepreneur in culinary sector of tourism in Aceh. The multiple regression method was used to analyse data. The approach used in this research are eight elements, namely Product, Partnership, Packaging, Programming, People, Place, Promotion and Price. The results showed that all variables simultaneously affect the entrepreneur in culinary sector of tourism.The most dominant affects is packaging element with 7,918 ≥ 1,985.